Monkeypox and pan-resistant Campylobacter spp infection in Entamoeba histolytica and Chlamydia trachomatis re-infection in a man who have sex with men. Issue 4 (October 2022) - Raccagni, Angelo Roberto; Mileto, Davide; Canetti, Diana; Tamburini, Andrea Marco; Rizzo, Alberto; Bruzzesi, Elena; Castagna, Antonella; Nozza, Silvia
Highlights: An MSM was diagnosed with monkeypox (MPX) and concurrent STI and STEIs. Sexual intercourse might be the predominant way of transmission of MPX. Physicians should be aware of MPX among individuals with a previous history of STIs. Presence of a concurrent STI should not rule out MPX infection and vice versa. Anoscopy might be helpful in revealing unnoticed MPX lesion.